FACTORS OF EDUCATING YOUNG PEOPLE IN THE SPIRIT OF PATRIOTISM - Axunov Ilkhom; Madaliev Rakhmiddin; Khasanov Nurmukhammad Khaydarali Ugli; Yusufjonov Kuyoshbek Komiljon Ugli (International Journal on Human-Computing Studies, 2021)
In this article, the recognition of our heritage by the peoples of the world, search, collection and analysis of research data, the lack of knowledge of some teachers about the methods and factors in educating future defenders of the Motherland, the need to focus on certain tasks in the learning process and using active-effect methods, it is about the tasks that need to be done with parents in educating young people in the spirit of patriotism.